2019
DOI: 10.1017/s1368980019003008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of anthropometric measurements and weight status perceptions reported by parents of 4-year-old children

Abstract: Objective:To assess the validity of self-reported height and weight by parents of 4-year-old children and subjective weight perception.Design:Descriptive cross-sectional study.Setting:Paediatric population living in the Autonomous Community of Madrid.Participants:Children born in 2008–2009 examined at 47–59 months of age. Data were collected by paediatricians of the Madrid Primary Care Physicians Sentinel Network. Parents reported weight and height data. Prevalence of weight status categories was calculated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…One of the limitations of our study is the use of self-reported data for participants aged 16 and over, or weight and height data reported by parents for the youngsters, which usually contribute to inaccurate estimations of children's adiposity. 42,43 It is also necessary to consider that institutionalized population are not included in our study, although in the case of children and adolescents this would represent a negligible percentage (approximately 0.28%). 21,44 In addition, the epidemiological questionnaire, that was mainly focused in COVID-19 risk factors, lacked key variables in the study of adiposity, such as dietary habits, physical activity or household income level, so it was not possible to evaluate their contribution to the observed geographical disparities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the limitations of our study is the use of self-reported data for participants aged 16 and over, or weight and height data reported by parents for the youngsters, which usually contribute to inaccurate estimations of children's adiposity. 42,43 It is also necessary to consider that institutionalized population are not included in our study, although in the case of children and adolescents this would represent a negligible percentage (approximately 0.28%). 21,44 In addition, the epidemiological questionnaire, that was mainly focused in COVID-19 risk factors, lacked key variables in the study of adiposity, such as dietary habits, physical activity or household income level, so it was not possible to evaluate their contribution to the observed geographical disparities.…”
Section: Resultsmentioning
confidence: 99%
“…One of the limitations of our study is the use of self‐reported data for participants aged 16 and over, or weight and height data reported by parents for the youngsters, which usually contribute to inaccurate estimations of children's adiposity 42,43 . It is also necessary to consider that institutionalized population are not included in our study, although in the case of children and adolescents this would represent a negligible percentage (approximately 0.28%) 21,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies like that of AlHasan et al ( 20 ) suggest that identifying overweight and obesity is more challenging in younger children, aged 2 to 4 years. Cultural beliefs associating early weight gain with health and well-being, and expectations of outgrowing overweight with growth and increased physical activity, may contribute to these perception differences, as discussed by Alshahrani et al ( 37 ) and Esteban-Vasallo et al ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sample is representative of the population of Community of Madrid, even with the selection bias mentioned above. Anthropometric measurements are based on objective criteria and were performed in a standardized way in all measurements, so they are subject to fewer validity errors, such as self-reported measures or those provided by parents 41 .…”
Section: Discussionmentioning
confidence: 99%